2021
DOI: 10.3390/jcm10214948
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Magnetic Resonance Imaging to Inform Clinical Decision-Making in Acute Spinal Cord Injury: A Systematic Review and Meta-Analysis

Abstract: The clinical indications and added value of obtaining MRI in the acute phase of spinal cord injury (SCI) remain controversial. This review aims to critically evaluate evidence regarding the role of MRI to influence decision-making and outcomes in acute SCI. A systematic review and meta-analysis were performed according to PRISMA methodology to identify studies that address six key questions (KQs) regarding diagnostic accuracy, frequency of abnormal findings, frequency of altered decision-making, optimal timing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 46 publications
0
20
0
1
Order By: Relevance
“…Recently, some parameters on conventional MRI study have been described such as intramedullary lesion length (IMLL) and maximal spinal canal compression (MSCC). The author's hypothesis is that these parameters could be used for prognostic purpose in addition to the preoperative ASIA score evaluation [13]. In parallel, the scientific community is increasingly turning its attention to more sophisticated imaging techniques for studying spinal cord injury and its clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some parameters on conventional MRI study have been described such as intramedullary lesion length (IMLL) and maximal spinal canal compression (MSCC). The author's hypothesis is that these parameters could be used for prognostic purpose in addition to the preoperative ASIA score evaluation [13]. In parallel, the scientific community is increasingly turning its attention to more sophisticated imaging techniques for studying spinal cord injury and its clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed to cause spinal cord injury including 1) hyperflexion causing spinal traction, 2) hyperextension causing extrinsic cord damage, and 3) edema or vascular injury causing parenchymal cord damage (Bonfanti et al, 2019;Ghaffari-Rafi et al, 2021;Mohanty et al, 2013) The severity of spinal cord injury (SCI) can range from transient to permanent injury. The least severe injury is known as neuropraxia, which is as a transient loss of motor or sensory function that last from 15 minutes to 48 hours (Jin et al, 2021).…”
Section: Transient Weaknessmentioning
confidence: 99%
“…Cases with complete spinal cord injury rarely improve. Those with incomplete type ofen improve but seldom regain normal function (Konovalov et al, 2020)((Ghaffari-Rafi et al, 2021)Bonfanti et al, 2019 (Martineau et al, 2019).…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…This Special Issue also includes three systematic reviews. The first of these, by Ghaffari-Rafi et al [ 14 ], assessed the role and impact of obtaining an MRI in acute SCI on clinical outcomes and decision making. Of the 32 studies included, MR imaging frequently identified pathologies such as spinal cord compression, ligamentous injury, and epidural hematoma that altered the acute management of SCI, including the need for surgery, timing of surgery, and the surgical approach (anterior vs. posterior).…”
mentioning
confidence: 99%